Groundwater abstraction: a model for saltwater intrusion of coastal fresh water (2017)
The knowledge of salinity level and intrusion of saltwater into freshwater aquifer is necessary for groundwater monitoring and prediction in the coastal areas. In this work, an advection-dispersion saltwater intrusion model is used to study and simulate saltwater intrusion in a typical coastal aquifer. The aquifer portion was divided into grid with elements and nodes. Map of the study area indicating well locations was overlain on the grid system such that these locations coincide with the nodes. Chlorides at these wells were considered as initial nodal salinities. Results showed a highest and lowest increase in simulated chloride of 37.89 mg/L and 0.8 mg/L respectively. It also revealed that the chloride concentration of most of the considered well may climb unacceptable level in the next few years, if the current abstraction rate continues unabated